2001
DOI: 10.1093/oxfordjournals.schbul.a006898
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Factors Influencing Adherence to a Continuous Neuroleptic Treatment Program in Schizophrenia Patients During 2 Years

Abstract: Dropout from prophylactic neuroleptic treatment is one major reason for relapse in schizophrenia patients. There is a lack of prospective studies on factors that predict medication adherence. We investigated factors suspected to predict dropout from continuous neuroleptic treatment in a 2-year prospective study involving 122 outpatients with a DSM-III-R diagnosis of schizophrenia. Forty-two (34.4%) were classified as patient-related dropouts. No significant difference between compliant patients and dropouts wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
2
17

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(99 citation statements)
references
References 61 publications
(93 reference statements)
4
75
2
17
Order By: Relevance
“…The evidence suggests that sociodemographic factors such as gender [Acosta et al 2009;Linden et al 2001] and family/marital status [Acosta et al 2009;Linden et al 2001] do not influence adherence as the association between nonadherence and these variables were not significant in most studies. However, results were mixed concerning ethnicity [Aldebot and de Mamani, 2009;Valenstein et al 2004], level of education [Acosta et al 2009;Aldebot and de Mamani, 2009;Hudson et al 2004;Janssen et al 2006;Linden et al 2001;Loffler et al 2003] and age [Acosta et al 2009;Linden et al 2001;Valenstein et al 2004]. Lack of insight was significantly associated with nonadherence in all studies [Acosta et al 2009;Aldebot and de Mamani 2009;Loffler et al 2003;Olfson et al 2006] except one [Linden et al 2001].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The evidence suggests that sociodemographic factors such as gender [Acosta et al 2009;Linden et al 2001] and family/marital status [Acosta et al 2009;Linden et al 2001] do not influence adherence as the association between nonadherence and these variables were not significant in most studies. However, results were mixed concerning ethnicity [Aldebot and de Mamani, 2009;Valenstein et al 2004], level of education [Acosta et al 2009;Aldebot and de Mamani, 2009;Hudson et al 2004;Janssen et al 2006;Linden et al 2001;Loffler et al 2003] and age [Acosta et al 2009;Linden et al 2001;Valenstein et al 2004]. Lack of insight was significantly associated with nonadherence in all studies [Acosta et al 2009;Aldebot and de Mamani 2009;Loffler et al 2003;Olfson et al 2006] except one [Linden et al 2001].…”
Section: Discussionmentioning
confidence: 91%
“…A prospective study [Loffler et al 2003] which studied subjective reasons for noncompliance among patients with schizophrenia reported that patients with more severe symptoms were less likely to consider relapse prevention as an important factor for their compliance [odds ratio (OR) 0.34; p = 0.009]. In contrast, another prospective study [Linden et al 2001] reported no prognostic relation between symptom severity Weiden et al [2004] Cross-sectional The survey involved 48 leading experts on adherence problems Rating by experts on scale from 1 to 10: poor insight (7.2), distress associated with side effects (7.2), lack of/partial efficacy with continued symptoms (6.9), belief that the medications are no longer needed (6.7), ongoing substance use problems (6.6)…”
Section: Disease-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of treatment dropout are reported less often; the figures for this range from 20% to 56% in patients with schizophrenia. [12][13][14] In patients with depression, the severity of the disorder has been associated with treatment dropout in some studies, [15] but not in all. [16] Agreeing with Last et al [15] Leserman [17] indicated that patients with depression were less likely to adhere to a treatment program than patients without depression and experienced worse outcomes in health.…”
Section: Introductionmentioning
confidence: 99%
“…Adherence to treatment refers to the degree of accordance between patient's behavior and professional's recommendations 6 . Approximately 20 to 50% of schizophrenic patients do not adhere to medication treatment [6][7][8][9][10] . Non-adherence rates ranges from 30 to 60% for patients with diagnostic of Schizophrenia, 51 to 69% for Major Depressive Disorder, 57% for Anxiety Disorders, 26 to 48% for Hyperactivity and Attention Deficit Disorder, and 35% for Substance Use Disorders 11 .…”
Section: Introductionmentioning
confidence: 99%